(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
Metaphysics is a monumental work in the history of world philosophy. It provides unprecedented inspiration for the contemplation of the “unknown,” serving as a cornerstone for both Eastern and Western philosophical reflections on the material world. The ancient Greek philosophers proposed many unsystematic, contradictory, and fragmented notions of cosmic origin and ontology. In Metaphysics, these concepts were collected and synthesised; Aristotle analysed and critiqued them through the logical framework of the “known” material philosophy. Eastern philosophy also possesses systematic metaphysical concepts and grapples with the paradox of “being” and “non-being” in its contemplation of the cosmic origin. The Taoist philosophy, centred on the I Ching, emphasises the dialectical unity of “being” and “non-being,” with the central theme being the Tao-change and balance. When Buddhist philosophy entered China, its ideas of cosmic origin fused with those of Taoism. Confucian scholars then developed the unified Confucian-Buddhist-Taoist cosmological doctrine, which reached its zenith during the Song Dynasty (Feng Youlan, 2013). However, the languages, text, and numbers developed from the “known” material philosophy continue to dominate human intellectual expression, and the debates persist. Relativity theory, quantum mechanics, and the three industrial revolutions have transformed human understanding from material science to energy science and information science, proving that matter is the mutual transformation between energy (non-material) and matter under the control of mechanical information. Thus, the cosmic and material origin lies in the dynamic interplay of information (non-material) and energy (non-material)-the yin-yang essence of existence-seeking and attaining balance through perpetual motion and transformation. At its root, the universe itself is the coexistence and evolution of material and non-material existence under the participation of information.